The Relationship Between Mental Toughness and Sports Anxiety in Volleyball Athletes - Khoirunisa , Nanda Tira Khoirunisa; Nugraha , Reshandi; Salman, Salman (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
In the game of volleyball, Athlete performance in volleyball is significantly influenced by psychological elements, particularly those related to anxiety and mental toughness. Mental toughness, which helps athletes manage their anxiety, is the capacity to handle stress while maintaining motivation, attention, and self-assurance. The purpose of this research is to ascertain how anxiety and mental toughness relate to 62 volleyball players between the ages of 15 and 21. The sports anxiety scale (Smith et al.) and the mental toughness measure (Gucciardi et al.) were used to gather data, evaluated using the correlation of product moments. Sport anxiety and mental toughness were shown to be significantly correlated negatively (coefficient -0.292, significance 0.021). Sports anxiety and mental toughness were discovered to be significantly correlated based on the data processing outcomes of this research. The analysis's findings indicate a strong negative association between mental toughness and sports anxiety. An athlete's anxiety decreases as their mental toughness increases, and vice versa.